The specific features of Guillain–Barré syndrome in Russia: Analysis of 186 cases - N. A. Suponeva; E. G. Mochalova; D. A. Grishina; M. A. Piradov (Нервно-мышечные болезни)
The medical records of 186 patients diagnosed with Guillain-Barré syndrome (GBS) who had been followed up at the Research Center of Neurology, Russian Academy of Medical Sciences, in 2000 to 2011 were retrospectively analyzed. Most (65 %) of the patients had severe GBS; 19 % of the patients were on mechanical ventilation (MV) for an average of 21 (13; 48) days. The forms of GBS, such as acute inflammatory demyelinating polyneuropathy (AIDP) (n = 141; 78 %), and axonal variants, such as acute motor axonal neuropathy (AMAN), acute sensorimotor axonal neuropathy (AMSAN), i. e. AMAN / AMSAN (n = 39; 22 %), were studied separately. There was a significant difference in the seasonal revalence (p < 0.05). AIDP was encountered evenly throughout the year; AMAN / AMSAN occurred in 46 % of cases in summer. AIDP was followed by acute respiratory viral infection in 35 % of cases; diarrhea wasby the axonal forms in 36 % (p < 0.05). The axonal forms ran a severer course than AIDP: MV was performed twice more frequently (33 and 15 %, respectively); its duration was 6‑fold longer: 90 (46; 102) and 15 (10; 21) days (p < 0.05). AMAN / AMSAN was characterized by a severer neurological status and disability in the acute period, as shown by the NIS, MRCss, INCAT, R-ODS, and Barthel scales; these patients showed a poorer response to pathogenetic therapy (p < 0.05): 59 % with an insufficient effect; 15 % of those with AIDP. After six years, the majority (84 %) of the patients with AIDP walked alone and only 16 % were assisted. In the same period, less than half of the patients (40 %) with AMAN / AMSAN walked alone and a third (29 %) could move with assistance and almost the same percentage (31 %) could not walk.Thus, a number of specific features of GBS were found in a Russian population (equal age and sex distribution; a larger percentage of the axonal forms than in European countries and the United States); however, the most characteristics did not differ from the global data.